2018
DOI: 10.1007/s00343-019-8308-5
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing of 16S rRNA amplicons characterizes gut microbiota shift of juvenile sea cucumber Apostichopus japonicus feeding with three antibiotics

Abstract: Sea cucumber Apostichopus japonicus is an important marine economic species in Asian countries due to its profound nutritional and medicinal value. So far, with the rapid development of intensifi ed artifi cial aquaculture of sea cucumbers, the use of antibiotics is still an inexpensive and dispensable way to treat pathogenic infections, especially during the nursery phase. However, there is little information on the eff ects of antibiotics on the intestinal microbiota of sea cucumber. Therefore an Illumina ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Therefore, at first glance, antibiotics do not appear to have a major effect on the organisms since the survival rate is not altered. Our results can be compared to studies in the sea cucumber Apostichopus japonicus , where Zhao et al [ 82 ] explored the effect of the antibiotics erythromycin, tetracycline, and norfloxacin for 15, 30, and 45 d. They showed that while they altered the growth rate of these animals in a time-dependent manner, there was no effect on their survival [ 82 ]. This contrast between antibiotics’ effect on survival versus physiology has been seen in other organisms.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, at first glance, antibiotics do not appear to have a major effect on the organisms since the survival rate is not altered. Our results can be compared to studies in the sea cucumber Apostichopus japonicus , where Zhao et al [ 82 ] explored the effect of the antibiotics erythromycin, tetracycline, and norfloxacin for 15, 30, and 45 d. They showed that while they altered the growth rate of these animals in a time-dependent manner, there was no effect on their survival [ 82 ]. This contrast between antibiotics’ effect on survival versus physiology has been seen in other organisms.…”
Section: Discussionmentioning
confidence: 84%
“…In a different study, Yamazaki and colleagues found that Rhodobacterales are the third most abundant order in the fecal microbiota of A. japonicus, and the relative abundances were significantly higher in larger animals than in smaller individuals (Yamazaki, et al, 2016). However, the subsequent article by Zhao and colleagues reported a decreased relative abundance of Rhodobacteraceae in A. japonicus juveniles when treated with either tetracycline or erythromycin, but an increase in sea cucumber survival and body weight (Zhao et al, 2019). The above summarized studies demonstrate how bacteria metabolic activity might play a key role in providing the energy source to hosts to facilitate or activate their cellular and molecular process.…”
Section: Examining the Microbe-echinoderm Associationsmentioning
confidence: 99%
“…The orders Rhodobacterales, Oceanospirillales, and Desulfobacterales were more abundant in larger animals. The long-term effects, in terms of growth and disease resistance, of disrupting the bacterial community of A. japonicus sea cucumbers by using antibiotics was also explored (Zhao et al, 2019). Interestingly, after administering different antibiotics (tetracycline, erythromycin, or norfloxacin), it was observed that some antibiotics increased the growth of the animals yet weakened their immunological system.…”
Section: Examining the Microbe-echinoderm Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sulfamethoxazole has the characteristics of low bioavailability and high water solubility. The large amount of unabsorbed antibiotics not only poses a serious ecological threat to the environment, but also severely disturbs the intestinal homeostasis of organisms and leads to the emergence of antibiotic-resistant strains ( Li et al, 2015 ; Zhao et al, 2019b ). Studies showed that although antibiotics control the occurrence of diseases to some extent, it also affects the structure of animal intestinal microflora, studies on the changes of intestinal microflora in aquaculture animals caused by antibiotics also attracted attention ( Stanton, 2013 ; Wang R. X. et al, 2015 ; Zhao et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%